Different Wave Structures for the (2+1)-Dimensional Korteweg-de Vries Equation - Chun-Rong Qin; Jian-Guo Liu; Wen-Hui Zhu; Guo-Ping Ai; M. Hafiz Uddin (Advances in Mathematical Physics)
In this article, a (2+1)-dimensional Korteweg-de Vries equation is investigated. Abundant periodic wave solutions are obtained based on the Hirota’s bilinear form and a direct test function. Meanwhile, the interaction solutions between lump and periodic waves are presented. What is more, we derive the interaction solutions among lump, periodic, and solitary waves. Based on the extended homoclinic test technique, some new double periodic-soliton solutions are presented. Finally, some 3D and density plots are simulated and displayed to respond the dynamic behavior of these obtained solutions.